Training and supervision in sport and exercise psychology - McCarthy, Paul 1977- (Routledge Taylor & Francis Group, 2024)
This book presents choices and challenges for trainees and supervisors, such as training and supervision mixing the science of doing sport and psychology with the art of decision-making to deliver services to athletes.
Description based on publisher supplied metadata and other sources
Keywords: Sportpsychologie